Drivers of Green Apparel Purchase in Indonesia: Willingness to Pay as a Moderator - Abdullah Dawamuz Zikri; Sri Rahayu Hijrah Hati (Binus Business Review, 2026)
In response to increasing environmental concerns and consumer demand, many apparel industries have adopted sustainable practices to reduce the environmental impact of textile waste and production processes. However, actual purchases of green products remain relatively low due to a gap between consumer intention and behavior. While previous studies have explored various determinants of green purchasing, limited research has integrated psychological factors from the Theory of Planned Behavior (TPB) with value-based constructs to explain this gap, particularly within Indonesia’s price-sensitive fashion market. This research investigated the factors influencing green apparel purchase intention and behavior in Indonesia by extending the TPB with additional variables: trust, green purchase value, environmental concern, environmental knowledge, and perceived consumer effectiveness. It also examined the moderating effect of Willingness to Pay. A quantitative approach was employed, using survey data from 496 Indonesian consumers, and the analysis was conducted using Structural Equation Modeling – Partial Least Squares (SEM-PLS). Results show that green purchase value significantly influences trust and attitude, while perceived consumer effectiveness, environmental concern, and environmental knowledge significantly affect attitude, subjective norms, and perceived behavioral control. Subjective norms significantly affect green purchase intention, which in turn significantly predicts green purchase behavior. Willingness to pay moderates the relationship between green purchase intention and green purchase behavior. The research contributes theoretical originality by bridging TPB and value-based perspectives and provides practical insights for businesses seeking to translate sustainable intentions into actual green apparel purchases in Indonesia.